2021
DOI: 10.1136/bmjopen-2020-046676
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 seroprevalence among hospital staff and preprocedural patients in Thai community hospitals: a cross-sectional study

Abstract: ObjectivesWe aimed to explore the seroprevalence of hospital staff comparing to preprocedural patients in Thai community hospitals to shed light on the situation of COVID-19 infection of frontline healthcare workers in low infection rate countries where mass screening was not readily available.DesignCross-sectional study.Setting52 community hospitals in 35 provinces covered all regions of Thailand.Participants857 participants consisted of 675 hospital staff and 182 preprocedural patients.Outcome measureCOVID-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We found a seroprevalence of 1.4% in the studies. This prevalence increases from the beginning of the fourth wave (April 2021) with 0.2% seropositive results [11,16].…”
Section: Discussionmentioning
confidence: 96%
“…We found a seroprevalence of 1.4% in the studies. This prevalence increases from the beginning of the fourth wave (April 2021) with 0.2% seropositive results [11,16].…”
Section: Discussionmentioning
confidence: 96%
“…However, a study conducted among hospitalized patients in Siriraj hospital, Bangkok province reported a SARS-CoV-2 prevalence of 7.5% during the February–April 2020 outbreak [ 20 ]. In addition, anti-SARS-CoV-2 IgM seroprevalence among asymptomatic staff working in community hospitals throughout the country and having close contact with infected patients during the outbreak was found 0.8–5.5% and IgG seroprevalence was 0.0–5.0% [ 21 23 ]. These IgM or IgG seroprevalence tend to be slightly higher than our results which mat reflect the higher exposure risk of health care workers in contact of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data on SARS-CoV-2 prevalence and seroprevalence in Thailand originated from infected individuals (hospitalized and recovered COVID-19 patients), close contacts with recovered COVID-19 patients and healthcare workers is available [ 20 23 ]. Data among asymptomatic/mild symptomatic and high exposure risk populations is still scarce, in particular Chiang Mai and Lamphun provinces, Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…A general agreement exists regarding the use of serology tests to support individual and outbreak management. Australia, India, Indonesia, Thailand, and Taiwan recognize the benefit of serology testing to [237,[256][257][258][263][264][265][266][267][268]:…”
mentioning
confidence: 99%
“…The Thai Department of Medical Science advises against antibody testing after receiving a COVID-19 vaccine [259]; • Members of the academic community have recommended using serology testing for preliminary screening to reduce the number of patients who visit the hospital, help predict the extent of infection in the future, detect hot spots, identify plasma donors [264][265][266], and detect asymptomatic individuals through mass screenings [267].…”
mentioning
confidence: 99%